Best Answer

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals".

The question is not clear.

Q: What is the answer to y square root of x 6subtracted 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

300*square root of 3 + 300*square root of 6 = 1254.462165

3/(4*square root(x)) ....Mukesh

729 does not have "a square root of 3 times 3 times 3 times 327" so the question does not arise. 729 is a square number with a square root of 3 x 3 x 3 because (3 x 3 x 3) x (3 x 3 x 3) = 729

You must be careful when multiplying square roots of negative numbers; the same rules that apply for normal square roots do NOT apply. I will use shorthand root(x) for the square root of x. For example, root(2) x root(3) = root(2 x 3) = root(6), but you can't do this with square roots of negative numbers. For example: root(-2) x root(-3) = i root(2) x i root(3) = i2 root(6) = (-1) root(6) = -root(6). "i" is the imaginary unit.

Square root of 49 = 7... Square root of 9 = 3... 3 x 7 = 21

Related questions

300*square root of 3 + 300*square root of 6 = 1254.462165

(x^2+x-1/2)= x(x+1)-1/2 [x + (1 - square root of 3)/2][x + (1 + square root of 3)/2] = 0 Check it: x^2 + x/2 + (square root of 3)x)/2 + x/2 + 1/4 + (square root of 3)/4 - (square root of 3)x/2 - (square root of 3)/4 - 3/4 = 0 x^2 + x/2 + x/2 + [(square root of 3)x]/2 - [(square root of 3)x]/2 + (square root of 3)/4 - (square root of 3)/4 + 1/4 - 3/4 = 0 x^2 + x - 2/4 = 0 x^2 + x - 1/2 = 0 How to find this roots: Using the completing the square method: x^2 + x - 1/2 = 0 x^2 + x = 1/2 x^2 + x + 1/4 = 1/2 + 1/4 (x + 1/2)^2 = 3/4 x + 1/2 = (plus & minus)(square root of 3/4) x = -1/2 + (square root of 3)/2 x = - 1/2 - (square root of 3)/2

3x^2 = 44 divide both sides by 3; x^2 == 44/3 x = +,- square root of 44/3 write 44 = 4 x 11; x = +,- 2(square root of 11/3) multiply the square root of 11/3 by square root of 3/3; x = +,- (2/3)(square root of 33)

5

square root of 4x is 2 times square root of x, so answer is square root of x times 3 since it is 2 square roots of x plus one of them

No. The Square root of x is not the value of x. So it can not be simplified beyond: Root X + root 3x Yes. The square root of 3x equals the square root of 3 times the square root of x, so when you add another square root of x, you can factor out the square root of x, thereby simplifying the expression to the square root of x times the sum of one plus the square root of three.

(x^2+x-1/2)= x(x+1)-1/2 [x + (1 - square root of 3)/2][x + (1 + square root of 3)/2] = 0 Check it: x^2 + x/2 + (square root of 3)x)/2 + x/2 + 1/4 + (square root of 3)/4 - (square root of 3)x/2 - (square root of 3)/4 - 3/4 = 0 x^2 + x/2 + x/2 + [(square root of 3)x]/2 - [(square root of 3)x]/2 + (square root of 3)/4 - (square root of 3)/4 + 1/4 - 3/4 = 0 x^2 + x - 2/4 = 0 x^2 + x - 1/2 = 0 How to find this roots: Using the completing the square method: x^2 + x - 1/2 = 0 x^2 + x = 1/2 x^2 + x + 1/4 = 1/2 + 1/4 (x + 1/2)^2 = 3/4 x + 1/2 = (plus & minus)(square root of 3/4) x = -1/2 + (square root of 3)/2 x = - 1/2 - (square root of 3)/2

3/(4*square root(x)) ....Mukesh

-2 and -3Check:(-2) + (-3) = -5(-2)(-3) = 6Thus -2 and -3 are not the required numbers. let's find them: x + y = -6xy = -5 y = -x -6x(-x - 6) = -5-x^2 - 6x = -5x^2 + 6x = 5x^2 + 6x + 9 = 5 + 9(x + 3)^2 = 14x + 3 = (+ & -)square root of 14x = -3 (+ & -)square root of 14x = -3 + square root of 14 or x = - 3 - square root of 14y = -x - 6y = 3 - square root of 14 - 6 or y = 3 + square root of 14 - 6y = -3 - square root of 14 or y = -3 + square root of 14Check:(-3 + square root of 14) + (-3 - square root of 14) = -6(-3 + square root of 14)(-3 - square root of 14) = -5 ?(-3)^2 - (square root of 14)^2 = -5 ?9 - 14 = -5Check also tow other numbers.

4 x square root of 10 minus square root of 10 = 3 x square root of 10.

root 27 = root 9 x root 3 = 3 root 3. Dividing this by root 3 gives 3!

729 does not have "a square root of 3 times 3 times 3 times 327" so the question does not arise. 729 is a square number with a square root of 3 x 3 x 3 because (3 x 3 x 3) x (3 x 3 x 3) = 729